Fashion upcycling : the DIY guide to sewing, mending, and sustainably reinventing your wardrobe - Hilado, Ysabel (Rocky Nook, 2023)
Save your wallet and the planet by repurposing older clothes and secondhand finds into fashionable new looks! In Fashion Upcycling, popular TikTok designer and Project Runway Junior contestant Ysabel Hilado shares her secrets for reinventing old clothing into dazzling new outfits. With several do-it-yourself, beginner-friendly projects and genius tips and tricks, you'll learn to express yourself and reinvent your closet in all-new ways. From dyeing faded clothes to easy ways to repurpose denim, there’s a project for everyone.